Demasculinization of X chromosomes in the Drosophila genus. - Sturgill, D.; Zhang, Y.; Parisi, M.; Oliver, B. (Nature, 2007)
X chromosomes evolve differently from autosomes, but general governing principles have not emerged. For example, genes with male-biased expression are under-represented on the X chromosome of D. melanogaster, but are randomly distributed in the genome of Anopheles gambiae. In direct global profiling experiments using species-specific microarrays, we find a nearly identical paucity of genes with male-biased expression on D. melanogaster, D. simulans, D. yakuba, D. ananassae, D. virilis and D. mojavensis X chromosomes. We observe the same under-representation on the neo-X of D. pseudoobscura. It has been suggested that precocious meiotic silencing of the X chromosome accounts for reduced X chromosome male-biased expression in nematodes, mammals and Drosophila. We show that X chromosome genes with male-biased expression are under-represented in somatic cells and in mitotic male germ cells. These data are incompatible with simple X chromosome inactivation models. Using expression profiling and comparative sequence analysis, we show that selective gene extinction on the X chromosome, creation of new genes on autosomes and changed genomic location of existing genes contribute to the unusual X chromosome gene content.